Peran Gaya Kepemimpinan Kepala Sekolah Terhadap Kinerja Dan Kompetensi Guru Di MTs Azzainiyyah Nagrog Sukabumi - Jalaludin Bulkini; Riswan Riswan; Siti Qomariyah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This research examines the impact of the school principal's leadership style on teacher performance and competence at MTs Azzainiyyah Nagrog, Sukabumi. A quantitative approach was employed, utilizing surveys to collect data from teachers at the school. The questionnaires focused on leadership styles implemented by the principal and teachers' perceptions of their performance and competence. The results demonstrate that the school principal's leadership style significantly influences teacher performance and competence. Leadership styles emphasizing teacher empowerment, effective communication, and support for professional development contribute to enhanced overall teacher performance and competence. Additionally, inspiring leadership and fostering a positive working climate further improve teacher performance and competence. The research emphasizes the crucial role of school principals in creating a conducive learning environment and motivating teachers to innovate and collaborate. Effective leadership goes beyond managerial aspects and extends to human resource development. The implications of the study are vital for school administrators, especially principals, to adopt more effective leadership strategies to enhance teacher performance and competence. Furthermore, this research enriches the academic knowledge in the field of education, specifically the relationship between school principal leadership styles and teacher performance and competence. Further studies could delve deeper into the factors affecting teacher performance and competence at MTs Azzainiyyah Nagrog. Exploring optimal school principal leadership development for better educational outcomes remains an area of interest for future investigation.